Investigation of the electrostatic potential of a grain boundary in Y-substituted BaZrO3 using inline electron holography. Issue 32 (31st July 2019) - Bondevik, Tarjei; Ness, Heine H.; Bazioti, Calliope; Norby, Truls; Løvvik, Ole Martin; Koch, Christoph T.; Prytz, Øystein
Abstract : The electrostatic potential experimentally measured across an individual BaZrO3 grain boundary. Abstract : We apply inline electron holography to investigate the electrostatic potential across an individual BaZr0.9 Y0.1 O3 grain boundary. With holography, we measure a grain boundary potential of −1.3 V. Electron energy loss spectroscopy analyses indicate that barium vacancies at the grain boundary are the main contributors to the potential well in this sample. Furthermore, geometric phase analysis and density functional theory calculations suggest that reduced atomic density at the grain boundary also contributes to the experimentally measured potential well.